Karakteristik Kimia pada Tanah Merah, Humus, dan Kapur: Implikasi untuk Pengelolaan Tanah dan Produktivitas Pertanian - Amanda Nur Fitria Ningrum; Haidar Fari Aditya; Chosa Zahro Fatiha; Ramadhani Mahendra Kusuma (G-Tech: Jurnal Teknologi Terapan, 2024)
Soil is the result of the transformation of minerals and organic matter from the surface to a certain depth. This process is influenced by various genetic and environmental factors, such as the properties of the parent material, climatic conditions, interactions with living organisms, topography, and changes that occur over a long period of time. This study aims to analyze the chemical properties of three different soil types—red soil, humus soil, and limestone soil—to understand their implications for soil management and agricultural productivity. The analysis was conducted at the Soil and Water Laboratory of UPT Agribusiness Development Malang from December 2023 to April 2024. The parameters tested included pH, P₂O₅ content, nitrogen, and K₂O. The results showed that limestone soil had the highest pH, phosphorus, and potassium values compared to red and humus soils, while all three types of soil had very low nitrogen content. This study highlights the importance of proper soil management to improve soil fertility and agricultural productivity.